The Distortion in the HIS Methods to Fuse Satellite Images - AbdulJabar, Hameed (Iraqi Journal of Science, 2024)
In this research three different HIS color modules had been studies as fusionmethods to fuse high special resolution monochromatic satellite image with lowspecial resolution colored satellite image for the same place to obtain high specialresolution colored satellite image, the color distortion and the intensity variation inthe resultant image had been studies and the solution to override them are presented.